Vaporizers in Adolescents: Associated Factors, Prevalence, and Community Perspective on Health Promotion - Ocasio-Peña, Carolina; Hernández Morla, Ubalmi (Horizonte Sanitario, 2022)
Objective: In the third of the Sustainable Development Goals: Health and Well-being, thereis a goal aimed at strengthening the prevention and treatment of substance abuse. Threeobjectives are proposed: (1) identify a bibliography regarding the use of vaporizers inadolescents and young people to verify important variables as associated factors, and (2)carry out a community compilation through interviews and forums to recognize the socialperception of the use of vaporizers, and (3) determine, in the population of Puerto Ricanyouth and adolescents, the prevalence of the use of vaporizers.Materials and methods: A mixed study: qualitative observational and cross-sectionalanalytical was carried out with data collection consisting of a review of 13 articles, interviewswith key informants who work with the health and safety of young Puerto Ricans, andanalysis, using the SPSS program, of the prevalence of the Puerto Rican self-administeredquestionnaire Consulta Juvenil as a secondary database (n=8,603).Results: The literature establishes associated factors such as marketing, family relationship,and socialization. It was found that organizations view community health promotion as apreventive method. 21.9% of high school students use vaporizers. 22.1% do not know thesubstance contained in their vaporizer.Conclusion: Health promotion is based on favorable public policies, health education, socialcommunitymobilization, and multidisciplinary work. We recommend that evaluations andprevention of the use of vaporizers be practiced based on health-promoting public health. Inthis way, the Sustainable Development Goal will be worked on: Health and Well-being forthe protection of young generations and to reduce the prevalence of substance use.Keywords: Vaporizers; Puerto Rico, Adolescents; Health Promotion.